(untitled) (Journal of Applied Oral Science, 2004)
The aim of this study was to evaluate the features of dentinal tubules occlusion following application of three commercially available desensitizing agents: potassium oxalate-based / Oxa-Gel (OX), HEMA and glutaraldehyde-based / Gluma Desensitizer (GD) and acidulated phosphate fluoride-based / Nupro Gel (AF). Buccal cervical areas of twenty-four extracted human third molars were smoothed and wet-polished with SiC papers and diamond pastes, in order to simulate the clinical aspect of hypersensitive dentin cervical surfaces. The teeth were randomly divided into four groups (n=6), according to the dentin surface treatments: G1: untreated; G2: OX; G3: GD; G4: AF. Specimens were fractured in the lingual-buccal direction and prepared for SEM analysis. OX promoted tubule occlusion by crystal-like deposits in the lumen of the tubules. While GL created a thin layer over the dentin surface, AF application produced precipitates that occluded the tubules. According to the SEM analysis, all desensitizing agents were able to occlude the dentinal tubules.